2012
DOI: 10.2109/jcersj2.120.272
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nanosized aluminum nitride powders by the cyanonitridation method

Abstract: Nanosized aluminum nitride (AlN) powders were prepared by calcining ¤-alumina (¤-Al 2 O 3 ) nanopowders under a flow of acetonitrile (CH 3 CN) diluted in argon. The nitridation process of ¤-Al 2 O 3 to AlN was monitored by powder X-ray diffraction patterns and 27 Al magic-angle spinning nuclear magnetic resonance spectroscopy. ¤-Al 2 O 3 began to be converted to AlN at 1050°C without ¤-¡ alumina transformation and the conversion was completed at 1300°C. The cyanide radical, which was produced by thermal decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…indicated that δ‐Al 2 O 3 converted to AlN without δ‐α alumina transformation. The change in XRD patterns with calcination temperatures was similar to that when using CH 3 CN or melamine except that the sample at 1000°C showed intense AlN peaks.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…indicated that δ‐Al 2 O 3 converted to AlN without δ‐α alumina transformation. The change in XRD patterns with calcination temperatures was similar to that when using CH 3 CN or melamine except that the sample at 1000°C showed intense AlN peaks.…”
Section: Resultssupporting
confidence: 57%
“…This temperature was similar to those for the nitridation of γ‐Al 2 O 3 in a mixture of NH 3 ‐C 3 H 8 and ammonolysis of δ‐Al 2 O 3 and was ca. 100°C higher than that for the cyanonitridation by CH 3 CN . The comparison between XRD patterns and NMR spectra demonstrated that the complete nitridation of Al 2 O 3 to AlN should be confirmed by both 27 Al MAS NMR spectroscopy and powder XRD.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations